Green History: Pembelajaran Sejarah Berbasis Ekopedagogi - Diki Tri Apriansyah Putra; Nur'aeni Marta; Muhammad Hasmi Yanuardi (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2026)
The current global environmental crisis requires the world of education and the discipline of history to take on a strategic role in building a new paradigm of ecological awareness in society. Looking at the practice of history education in Indonesia today, it is still dominated by discussions of political, social, and economic events. Green history is a new approach to history that attempts to connect historical events, local wisdom, and cultural systems with ecological awareness. This article aims to examine a new approach to history learning by integrating ecological values into the learning process. The method used is historical with a literature study approach. The results of the study show that green history places nature as a historical actor by emphasizing ethical and sustainability dimensions in historical interpretation. Integrating it with ecopedagogy means that history learning does not merely focus on conveying the chronology of past events, but also serves as a reflective tool for understanding the historical roots of the current ecological crisis. Green history acts as a new paradigm in history education that is oriented towards ecological intelligence, environmental and climate justice, and the transformation of students behavior towards sustainable educational practices.